Incrimination of Aedes aegypti and Aedes albopictus as vectors of dengue virus serotypes 1, 2 and 3 from four states of Northeast India. Issue 4 (26th March 2020) - Chetry, Sumi; Patgiri, Saurav Jyoti; Bhattacharyya, Dibya Ranjan; Dutta, Prafulla; Kumar, N. Pradeep
Abstract : Dengue is an important vector borne disease with a great public health concern worldwide. Northeast India has experienced dengue almost every year for a decade. As studies on dengue vectors from this region are limited, we undertook an investigation to detect natural infection of the dengue virus (DENV) in potential dengue vectors of this region. Adult Aedes mosquitoes which were collected were subjected to RT-PCR for detection of infecting dengue serotype. Minimum infection rate was also determined for each positive pool. Out of the total 6229 adult Aedes mosquitoes collected, Aedes aegypti (63.3 %) was abundant in comparison to Aedes albopictus (36.7 %). These specimens (515 mosquito pools) were subjected to RT-PCR for detection of DENV-1, 2, 3 and 4. RT-PCR revealed the existence of DENV in both male as well as female mosquito pools suggesting natural transovarial transmission of DENV in this region. A total of 54 pools tested were positive for DENV-1, 2, 3 serotypes. This study revealed the occurence of DENV in both the potential dengue vectors from this region along with evidence of transovarial transmission which helps in persistence of the virus in nature.